Low-loss paper-substrate triple-band-frequency reconfigurable microstrip antenna for Sub-7 GHz applications - Ajit Kumar, Singh; Santosh, Kumar Mahto; Rashmi, Sinha; Alibakhshikenari, Mohammad; Al Gburi, Ahmed Jamal Abdullah; Ahmad, Ashfaq; Kouhalvandi, Lida; Virdee, Bal S.; Dalarsson, Mariana (MDPI, 2023)
In this paper, a low-cost resin-coated commercial-photo-paper substrate is used to design a printed reconfigurable multiband antenna. The two PIN diodes are used mainly to redistribute the surface current that provides reconfigurable properties to the proposed antenna. The antenna size of 40 mm × 40 mm × 0.44 mm with a partial ground, covers wireless and mobile bands ranging from 1.91 GHz to 6.75 GHz. The parametric analysis is performed to achieve optimized design parameters of the antenna. The U-shaped and C-shaped emitters are meant to function at 2.4 GHz and 5.9 GHz, respectively, while the primary emitter is designed to operate at 3.5 GHz. The proposed antenna achieved peak gain and radiation efficiency of 3.4 dBi and 90%, respectively. Simulated and measured results of the reflection coefficient, radiation pattern, gain, and efficiency show that the antenna design is in favorable agreement. Since the proposed antenna achieved wideband (1.91–6.75 GHz) using PIN diode configuration, using this technique the need for numerous electronic components to provide multiband frequency is avoided.